La Gestion LOcale SÉcurisée (GELOSE) : L’expérience malgache de gestion décentralisée des ressources naturelles - Bruno Sarrasin (Études Caribéennes)
Marked by exceptional biodiversity and extreme human poverty, Madagascar is experiencing a rapid destruction of its natural resources, placing territory and its appropriation at the heart of development issues. From this perspective, this article will look at the development and implementation of a public policy, the Gestion LOcale SÉcurisée (GELOSE), for the local management of natural renewable resources. This regulation seeks to transfer the management of these resources from the government to local communities in the goal of protecting them more effectively. We will see, however, that the objectives, resources and strategies of the primary actors concerned are difficult to reconcile at best and that the relational system to which the policy gives rise is not necessarily in keeping with the goals being pursued.